Legal Protection for Hospitals Regarding Decisions for Patients Requesting Independent Referrals - Priscilla; Hanekung Titisari Santoso; Orpa Wati; Lidwina Grasia Natasya Dappa (PT. Caesarindo Triloka Persada, 2025)
This study analyzes the factors that encourage patients to make self-referrals, and examines the legal responsibilities related to complications or deaths in the process. In addition, this study examines the legal protection for hospitals that follow standard procedures. The methods used are literature studies and analysis of laws and regulations. The results of the study indicate that self-referral functions as a mechanism for delegating tasks in structured health services, aiming to ensure that patients receive services that are in accordance with their medical needs. Factors that influence self-referrals include family perceptions of the patient's condition, previous service experiences, and social and economic factors. However, hospitals still have an obligation to provide accurate information and carry out initial treatment before referring patients. Legal protection for hospitals is provided if they have carried out standard medical procedures and obtained written consent from the patient or their family. Therefore, documentation of medical actions and education to patients are important aspects in minimizing possible legal risks.